Gestational, perinatal and family findings of patients with Patau syndrome - Rafael Fabiano M. Rosa; Melina Vaz Sarmento; Janaina Borges Polli; Daniela de Paoli Groff; Patrícia Petry; Vinícius Freitas de Mattos; Rosana Cardoso M. Rosa; Patrícia Trevisan; Paulo Ricardo G. Zen (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To describe gestational, perinatal and family findings of patients with Patau syndrome (PS). METHODS: The study enrolled patients with PS consecutively evaluated during 38 years in a Clinical Genetics Service of a pediatric referral hospital in Southern Brazil. The clinical data and the results of cytogenetic analysis were collected from the medical records. For statistical analysis, the two-tailed Fisher's exact test and the chi-square test with Yates' correction were used, being significant p<0.05. RESULTS: The sample was composed of 27 patients, 63% were male, with a median age of nine days at the first evaluation. Full trisomy of chromosome 13 was the main cytogenetic finding (74%). Only six patients were submitted to obstetric ultrasound and none had prenatal diagnosis of PS. The patients' demographic characteristics, compared to born alive infants in the same Brazilian state showed a higher frequency of: mothers with 35 years old or more (37.5%); multiparous mothers (92.6%); vaginal delivery (77%); preterm birth (34.6%); birth weight <2500g (33.3%), and Apgar scores <7 in the 1st (75%) and in the 5th minute (42.9%). About half of them (53%) died during the first month of life. CONCLUSIONS: The understanding of the PS patients' gestational, perinatal and family findings has important implications, especially on the decision about the actions to be taken in relation to the management of these patients.